Real life stories when one has a disability in the time of COVID-19 - Phillips, Julie; Kirk, Rea (Research and Humanities in Medical Education, 2020)
With the COVID-19 pandemic, many challenges and problems have occurred across all populations; however, for individuals with disabilities, the challenges are often significantly exacerbated by the additional problems of access and inequity. This article describes five real life stories of individuals with disabilities who have been seriously impacted by the pandemic. We have described the individuals' disabilities, the complexity of the situations amplified by the pandemic, and how it has jeopardized the health of these individuals. As these individuals navigated this new unchartered territory of COVID-19, they often were left with few resources and an inability to access their traditional resource networks. We have documented each story and integrated relevant sources that support the jeopardy of the individual involved. We hope that this article may assist readers in understanding the perils of progressing through COVID-19 with a disability.